Morphology of preimaginal stages of Lauxania and Calliopum (Diptera: Lauxaniidae) - Semelbauer, Marek; Kozánek, Milan (Zootaxa, 2012)
Scanning electron microscopy (SEM) analysis of all preimaginal stages of the following lauxaniid species is presented for thefirst time: Lauxania cylindricornis (Fabricius), L. minor Martinek, Calliopum aeneum (Fallén), C. elisae (Meigen), C.splendidum Papp and C. simillimum (Collin). Detailed images of the pseudocephalon, antenna, maxillary palpus, facial mask,cirri, mouth hooks, body segments and anterior and posterior spiracles of all larval instars are provided along with illustrationsof the cephaloskeleton for all three instars. Eggs bear longitudinal ridges and a perforated tubercle on the posterior end. Larvaehave several rows of cirri, a pair of abdominal ambulatory lobes and the distal part of Malpighian tubules is filled with whitematter. Identification of species or genera is problematic especially in the second instar. Puparia are barrel-shaped, while thecalcareous deposit over the puparium typical for other lauxaniids is missing. The morphology of the immature stages supports the notion that Lauxania may be not monophyletic.